2014
DOI: 10.1371/journal.pone.0087835
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Based Transcriptome Analysis of Hepatitis E Virus (HEV) and Hepatitis B Virus (HBV) Replicon Transfected Huh-7 Cells

Abstract: Pathogenesis of hepatitis B virus (HBV) and hepatitis E virus (HEV) infection is as varied as they appear similar; while HBV causes an acute and/or chronic liver disease and hepatocellular carcinoma, HEV mostly causes an acute self-limiting disease. In both infections, host responses are crucial in disease establishment and/or virus clearance. In the wake of worsening prognosis described during HEV super-infection over chronic HBV hepatitis, we investigated the host responses by studying alterations in gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 56 publications
1
36
0
Order By: Relevance
“…Growing evidence suggests that microRNA editing might involve immune responses to virus infection. During HCMV infection, edited miR-376 down-regulates the expression of HLA-E which promotes NK cell ability to eliminate the HCMV infected cells60. Further study showed that microRNA editing occurred in pre-miRNA-126, pre-miRNA-744 in Tongcheng and in pre-miRNA-27a in Landrace at 3, 5 and 7 dpi (Supplementary Table S5).…”
Section: Discussionmentioning
confidence: 95%
“…Growing evidence suggests that microRNA editing might involve immune responses to virus infection. During HCMV infection, edited miR-376 down-regulates the expression of HLA-E which promotes NK cell ability to eliminate the HCMV infected cells60. Further study showed that microRNA editing occurred in pre-miRNA-126, pre-miRNA-744 in Tongcheng and in pre-miRNA-27a in Landrace at 3, 5 and 7 dpi (Supplementary Table S5).…”
Section: Discussionmentioning
confidence: 95%
“…Recent RNA-seq analyses of HBV-expressing Huh7 cells [254] and primary rat hepatocytes [186] also detected decreased expression of GLUT2, the main hepatic glucose transporter. Investigation of the effect of fasting glucose levels on HBV replication revealed a link, albeit minor, between the metabolic state of the cell and the level of HBV replication, [245] and both gluconeogenesis and lipogenesis are under the same transcription factor control as HBV replication.…”
Section: Hbv and Hccmentioning
confidence: 99%
“…At various time points, post incubation (12, 24, 36, 48, 72 h; data shown for only 48 h), the cells were observed under confocal microscope using Hybrid detector (HyD) at 561 nm to check the fluorescence from RFP protein. Similar experiments were conducted for pORF2-VLPs encapsidated with 5′-methyl-G-HEV( 1 – 249 nt )- HBsAg RNA and Indirect immunofluorescence assay was performed and [ 7 ] observed under inverted fluorescent microscope (Nikon TE2000-U) for the expression of HBsAg protein. The entry and internalization of pORF2 f-VLP’s (produced from ORF2-linker EGFP protein) has been previously demonstrated by us in Huh-7 cells [ 1 ].…”
Section: Resultsmentioning
confidence: 99%